Optimisation of a novel glass-alginate hydrogel for the treatment of intracranial aneurysms. (15th November 2017) - Brady, S.A.; Fox, E.K.; Lally, C.; Clarkin, O.M.
Highlights: Hydrogels composed of alginate, an ion releasing glass and glucono-delta-lactone were produced. The hydrogel working time is governed by the chemical composition of the alginate. The hydrogel hardening time is governed by the molecular weight of the alginate. The gelation rate of the hydrogel is slow compared to typical alginate hydrogels. Abstract: The current gold standard for aneurysm treatment is endovascular coiling. However, recurrence is observed in over 20% of cases. A novel hydrogel has been developed to treat aneurysms. This hydrogel is composed of a polymeric alginate, a novel ion releasing glass and glucono-delta-lactone. This is an internally setting alginate hydrogel, wherein the setting rate can be controlled by both the glass and the alginate chemistry. The aim of this work is to examine the effect of each component of the hydrogel and optimise the composition of the hydrogel, specifically the alginate molecular weight, M/G ratio and concentration. The effects of gamma sterilisation will also be examined. The results show that alginate concentration, chemical composition and molecular weight affect the compressive strength, working time, hardening time and deliverability of the hydrogel. Gamma irradiation of the alginate reduces the molecular weight, which has a negative effect on the usability of this hydrogel.